“A światłość w ciemności świeci...” Konfrontacja światłości z ciemnością w Ewangelii Janowej - Piekarz, Danuta (Verbum Vitae, 2016)
The symbolism of light and darkness, well known to the authors of the Old Testament, appears particularly often in the Gospel according to St. John. While it is relatively easy to guess that for the writer the symbol of light represents the active presence of Christ in the world, it is much harder to identify precisely the symbolism – undoubtedly negative – of the darkness. On this point commentators have differed very much in their opinions. The biblical image of light joins inseparably a cognitive dimension and a moral one: the light allows us to get to know God, marking the way to Him, and at the same time reveals the truth of human deeds. That is why evildoers avoid the light, hiding their deeds in darkness. In the theology of St. John, the Passion of Christ is presented as a time when darkness prevails, yet its victory is only a brief illusion. Following the night of Passion, the dawn of the Resurrection approaches.